2005
DOI: 10.1002/polb.20479
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing quantum efficiency of MEH‐PPV through the reduction of chain aggregations by thermal treatments

Abstract: The quantum efficiencies of photoluminescence (PL) and electro‐luminescence (EL) of poly[2‐methoxy‐5‐(2′‐ethyl‐hexyloxy)‐1,4‐phenylenevinylene] (MEH‐PPV) were significantly increased by heat treatments under vacuum with further removing the undissolved portion. The UV–vis absorption was found to decrease with heating time, while PL intensity increased. The maximum PL quantum yield was 6.5 times that of the untreated MEH‐PPV, which was attributed to the reduction of chain aggregations and the interruption of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…For MEH‐PPV(I), the broken polymer segments during thermal treatment at 200 °C were highly reactive and tended to chemically bond to the adjacent polymer chains, provoking a reduction of chain aggregation. As a result, the PL quantum efficiency in film form was increased to ∼6 times that of untreated MEH‐PPV 16…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For MEH‐PPV(I), the broken polymer segments during thermal treatment at 200 °C were highly reactive and tended to chemically bond to the adjacent polymer chains, provoking a reduction of chain aggregation. As a result, the PL quantum efficiency in film form was increased to ∼6 times that of untreated MEH‐PPV 16…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we have mistakenly attributed the peak at δ = 6.6–6.7 ppm for the MEH‐PPV prepared from monomer I to the formation of cis ‐vinylene bonds during Gilch polymerization 15. As the resulting polymer was subjected to thermal treatment at 200 °C for 1–2 h, half of the methylene bonds were broken as indicated by the decrease of the peak at δ = 6.6–6.7 ppm 16. In this study, we have also found that the MEH‐PPV(I) began to degrade at ∼200 °C, but that the major degradation took place at 367 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, polymer light‐emitting diodes (PLEDs) have attracted much attention for applications in large size flexible displays1–3 because of their simple structure and facile fabrication using soluble coating methods4, 5 (spin coating or ink‐jet printing). The PLED is the current operational device which emits light through the recombination of excitons injected from the anode and cathode electrodes.…”
Section: Introductionmentioning
confidence: 99%